Implementation Of Community Based Tourism Concept In Sustainable Tourism Management In Penglipuran Village - I Kadek Ery Pradnyantara; Ni Putu Nina Eka Lestari (Institute of Computer Science (IOCS), 2021)
The development of a tourism village can positively impact the village community itself, including the existence of new jobs for the community so that it can reduce the unemployment rate in the village. Apart from the concept of ecotourism, tourism villages can also make a village an independent village because they can provide alternatives. Jobs that the local community can enter.This research uses a qualitative approach. The location in this study is Penglipuran Village, Bangli Regency, Bali Province. The sample in this study was taken using purposive sampling, while the information is the Operational Coordinator, Tourist Site Manager, and Penglipuran Tourism Village Community. Data were collected by in-depth interviews, field observations, and documentation. The data analysis uses triangulation with the data reduction stage, the data presentation stage, and the conclusion and verification stages. The results of the study show that the application of the concept of community-based tourism is proven to be able to improve future sustainable tourism in Penglipuran Village because conceptually, the principle of community-based tourism development is to place the community as the main actor of development through empowerment in various tourism activities so that the maximum benefits of tourism are felt directly by the society.